1999
DOI: 10.1029/1999jb900079
|View full text |Cite
|
Sign up to set email alerts
|

Two‐dimensional anisotropic tomography of lithosphere beneath France using regional arrival times

Abstract: Abstract. This paper presents an anisotropic tomography study beneath France. Travel times of P• waves were inverted in order to simultaneously retrieve lateral variations of both seismic velocity and seismic anisotropy within the subcrustal lithosphere. The parameterization scheme uses a "classical" approach. The subcrustal lithosphere is modeled using a two-dimensional horizontal grid of nonoverlapping cells (0.5 ø x 0.5ø), each cell being characterized by an average slowness (the isotropic term of slowness)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
15
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 38 publications
(17 reference statements)
6
15
2
Order By: Relevance
“…The fast shear wave polarization plane is usually oriented parallel to the belt, and the delay between the fast and slow S-wave arrivals is larger than 1 s, even beyond the Mesozoic Pyrenees belt. Pn anisotropy measurements (Judenherc et al 1999) are in good agreement with S-wave splitting measurements; the fast propagation direction of Pn is also parallel to the Hercynian/Pyrenean tectonic fabric, suggesting that the entire lithosphere beneath the probed area has a coherent 'wrench fault type' fabric. The analysis of the seismic anisotropy data for the active orogen of Taiwan, the Neoproterozoic Ribeira belt and the Hercynian/Alpine Pyrenean belt leads to similar conclusions.…”
Section: T R a N S P R E S S I O N A L O R O G E N I C D O M A I N Ssupporting
confidence: 69%
“…The fast shear wave polarization plane is usually oriented parallel to the belt, and the delay between the fast and slow S-wave arrivals is larger than 1 s, even beyond the Mesozoic Pyrenees belt. Pn anisotropy measurements (Judenherc et al 1999) are in good agreement with S-wave splitting measurements; the fast propagation direction of Pn is also parallel to the Hercynian/Pyrenean tectonic fabric, suggesting that the entire lithosphere beneath the probed area has a coherent 'wrench fault type' fabric. The analysis of the seismic anisotropy data for the active orogen of Taiwan, the Neoproterozoic Ribeira belt and the Hercynian/Alpine Pyrenean belt leads to similar conclusions.…”
Section: T R a N S P R E S S I O N A L O R O G E N I C D O M A I N Ssupporting
confidence: 69%
“…Another difference between the seismic anisotropy observed by this work and on the Iberian Peninsula is in the degree of anisotropy. On land, in both the Pyrenees (Judenherc et al 1999) and in the Ossa Morena Zone (Díaz et al 1993), a 3–5 per cent anisotropy was observed, whereas in this work, higher values of 5–8 per cent were seen.…”
Section: Discussioncontrasting
confidence: 69%
“…There, the fast direction determined in the mantle from the ILIHA Deep Sounding Seismic experiment, from a limited sampling of azimuths, was 040° in the Ossa Morena Zone, southwest Iberia (Díaz et al 1993). From regional P n tomography, the fast direction is roughly E–W in the Pyrenees, corresponding to the strike and possible ‘shear’ of that mountain chain (Judenherc et al 1999). Smith & Ekström (1999), using earthquake P n arrivals, found that the fast direction at a station in the southeast of the peninsula was northeast–southwest and on the east coast, it was more eastnortheast–westsouthwest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The negative delays (nearly 0.5 s) in northern Africa could be explained in the same way. On the other hand, to the north and northwest the negative delays (from 0.2 to 0.5 s) could reflect the moderate crustal thinning toward the Iberian massif and/or would be an effect of the old and stable Hercynian crust (Judenherc et al, 1999). One of the longest negative delays (>0.5 s) was obtained at the station on the south Portuguese coast (near Faro).…”
Section: Station Delaysmentioning
confidence: 86%